Self-Efficacy Memediasi Transformational Leadership Terhadap Kinerja Pegawai - Rahman, Muhammad Syauqi Taufiqur (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2023)
The amount to which the leadership function is performed will have a significant impact on the organization's ability to achieve the company goals that have been established by the corporation. Looking into employees' creative self-efficacy is one thing that leaders need to do in order to boost employee performance. State-owned PT Pos Indonesia has the greatest service network that is dispersed over the entire nation. PT Pos Indonesia (Persero) is now undergoing changes related to its operations, human resources, subsidiaries, and product development. However, PT Pos Indonesia also competes fiercely with other businesses of a similar nature, such JNE, J&T, Tiki, Sicepat, etc. The purpose of this study is to examine and ascertain the impact of transformational leadership on employee performance at PT. Pos Indonesia Bandung through creative self-efficacy. The research methodology makes use of questionnaire-based data collecting, descriptive and verification methodologies, and the SmartPLS 3.3.3 analysis tool. The sampling technique combines convenience sampling with nonprobability sampling. The findings of this study demonstrate that transformational leadership significantly and favorably impacts employee performance. Transformational leadership has a favorable and considerable impact on creative self-efficacy. Employee performance is positively and significantly impacted by creative self-efficacy. Then, through creative self-efficacy, transformational leadership has a substantial impact on staff performance.